Prospects of robotics using during elimination of consequences of emergency situations - Kondratovich Александр Андреевич; Dmitrichenko Геннадий Степанович (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
This article depicts relevance and necessity of rescue robotic device creation, considers possible ways of possible damages reducing for rescuers during elimination of emergency situations, determines objects on the territory of the Republic of Belarus where robotic rescue devices can be used.